Sana for all: An analysis of “sana all” using sakop - Dawis, Alexis Rain M. (Animo Repository, 2024)
The emergence of new words and phrases brings about new avenues of communication and expression. This is just as true for slang and colloquial language as it might be for formal language. This paper aims to analyze the slang phrase turned colloquial phrase “Sana All” that comes from the Filipino Language, how the phrase functions and how it shows Filipinos’ collectivist values. It aims to ask and attempt to answer what the phrase does, how it works and why it is used in particular social settings and groups or sakop as defined by Leonardo Mercado. The structure of the phrase will be studied, as well as its sudden rise in usage, its various possible usages, and the intentions behind how it is used. This will be done to show how Sana All’s impact on the people who use it and those that they express it to. This study will look into how online blogs, vlogs and social media choose to describe the phrase in order to determine what those who use it claim or believe it to be. As it stands, this paper is a conceptual analysis of the phrase “Sana All” with sakop as a framework and will attempt to create coherent description of Sana All, taking into consideration the differing definitions from both formal and informal sources in order to not only study a linguistic phenomenon but also show off a uniquely Filipino expression and the way it handles interacting with people in the world both online and in the real world.